Enhancing Food-Entrepreneurship Skills of University Students Through Training in Burger Production And Its Entrepreneurial Experience - Arief Putra, Aronal; Sandra, Afriani; Novia, Deni; Fitri Kurnia, Yulianti; Rahmi, Elfi (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2023)
Burgers are processed foods that are interesting to develop as one of the entrepreneurs' products. Training in burger making and providing entrepreneurial experience to the participants as a form of community service were conducted. Implementation of this activity includes preparation, participant admission, production training, and product selling. Patty formulation, patty molding, contact grilling, burger plating, packaging, and selling were conducted during practice. From this activity, enhancing the knowledge and skill of participants during production in the processing room and selling in campus areas are significant to creating the essential entrepreneur ability. The development of character and spirit of entrepreneurship and profit gaining during selling represents the enlarged passion of the participant toward the real entrepreneurship environment. Further guidance is required to encourage the participant to transform into a start-up business